Marginal adaptation, physicochemical and rheological properties of treated dentin matrix hydrogel as a novel injectable pulp capping material for dentin regeneration - Ahmed A. Holiel; Eman M. Sedek (BMC, 2023)
Abstract Background Treated dentin matrix hydrogel (TDMH) has been introduced as a novel injectable direct pulp capping material. In this regard, this study aimed to evaluate its marginal adaptation, physicochemical and rheological properties for the development of clinically feasible TDMH. Methods TDMH was applied to the pulp floor of prepared Class I cavities (n = 5), marginal adaptation was assessed by SEM at 1000 X magnification to detect gap between dentin and filling material. Five syringes were filled with TDMH and placed between the compression plates of a universal testing machine to evaluate injectability and gelation time was also evaluated by test vial inverting method. The microstructures of lyophilized TDMH were observed by SEM. Moreover, TDMH discs (n = 5) were prepared and the water uptake (%) was determined based on the equilibrium swelling theory state of hydrogels. Its solubility was measured after one week by the ISO standard method. Rheological behaviours of TDMH (n = 5) were analysed with a rotational rheometer by computing their complex shear modulus G* and their associated storage modulus (G') and loss modulus (G''). Statistical analysis was performed using F test (ANOVA) with repeated measures and Post Hoc Test (p = 0.05). Results TDMH presented an overall 92.20 ± 2.95% of continuous margins. It exhibited gelation during the first minute, and injectability mean was 66 ± 0.36%. TDMH showed a highly porous structure, and the pores were interconnected with an average diameter about 5.09 ± 3.17 μm. Swelling equilibrium gradually reached at 6 days up to 377%. The prepared hydrogels and maintained their shape after absorbing over three times their original weight of water. TDMH fulfilled the requirements of ISO 6876, demonstrating a weight loss of 1.98 ± 0.09% and linear viscoelastic behaviour with G` 479.2 ± 12.7 and G`` 230.8 ± 13.8. Conclusions TDMH provided good marginal adaptation, appropriate physicochemical and viscoelastic properties support its use as a novel direct pulp capping material in future clinical applications.